2016
DOI: 10.3892/etm.2016.3014
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of microRNA-202 is associated with the metastasis of esophageal squamous cell carcinoma

Abstract: Abstract. The present study aimed to determine the expression levels and biological functions of in patients with esophageal squamous cell carcinoma (ESCC). A total of 60 patients with ESCC and 30 healthy individuals were enrolled and reverse transcription-quantitative polymerase chain reaction was performed to measure the expression levels of miR-202. In order to investigate the effects of miR-202 expression levels on the proliferative, migratory and invasive abilities of ESCC cells, methylthiazolyl-tetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In oesophageal squamous cell carcinoma, miR-202 is poorly expressed in tumour tissues and inversely correlated with the degree of cell differentiation and lymph node metastasis. In addition, miR-202 is decreased in the peripheral blood of oesophageal squamous cell carcinoma patients and significantly associated with the development, invasion and metastasis of oesophageal squamous cell carcinoma (37). Moreover, low expression levels of miR-202 are observed in multiple myeloma (24), colorectal cancer (22), hepatocellular carcinoma (25), lung (38) and cervical cancer (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oesophageal squamous cell carcinoma, miR-202 is poorly expressed in tumour tissues and inversely correlated with the degree of cell differentiation and lymph node metastasis. In addition, miR-202 is decreased in the peripheral blood of oesophageal squamous cell carcinoma patients and significantly associated with the development, invasion and metastasis of oesophageal squamous cell carcinoma (37). Moreover, low expression levels of miR-202 are observed in multiple myeloma (24), colorectal cancer (22), hepatocellular carcinoma (25), lung (38) and cervical cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that the restoration of miR-202 expression suppresses cervical cancer cell growth and metastasis (39). Ma et al reported that ectopic expression of miR-202 inhibits cell proliferation, migration and invasion and induces cell apoptosis of oesophageal squamous cell carcinoma (37,41). Meanwhile, Jiang et al (38) demonstrated that the upregulation of miR-202 decreases cell proliferation and improves the G0/G1 cell cycle arrest and apoptosis in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-202 may also play an important role in different cancers. For example, miR-202 suppressed cell proliferation in EC by targeting FOXR2 [10], and low miR-202 expression was shown to contribute to migration and invasion of esophageal squamous cell carcinoma cells [11]. However, whether miR-202 regulates EMT and cell migration and invasion in EC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports, which has been shown that the expression of miR-202 is downregulated in cervical cancer [28], lung cancer [21], hepatocellular carcinoma [29], colorectal cancer [20], and multiple myeloma [30]. In oesophageal squamous cell carcinoma, the miR-202 showed low level of expression in tumour tissues and its expression was signi cantly correlated (negative correlation) with lymph node metastasis and cell differentiation [31]. It is documented that the miR-202 expression in gastric cancer is also downregulated in tumour tissues and showed an inverse correlation with age and tumour size [22].…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, restoration of miR-202 increased apoptosis and G0/G1 cell cycle arrest and suppressed cell proliferation in lung cancer cell line [21]. Studies on oesophageal squamous cell carcinoma showed that upregulation of miR-202 could suppresses invasion, migration, proliferation and also, increase cell apoptosis [31,33]. Together, these ndings clarify that the miR-202 could be introduced as an important biomarker in these cancers and may serve as a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%